Kesulitan Guru dalam Mengajar Peserta Didik yang Tidak Berlatar Belakang PAUD/TK di SD Negeri 46 Banda Aceh - Febriani, Sintia; Sulaiman, Sulaiman; Israwati, Israwati (Universitas Syiah Kuala, 2024)
Abstract (English)This research is entitled teacher's difficulties in teaching students who do not have an early childhood/kindergarten background in class I SD Negeri 46 Banda Aceh. The teacher's difficulty in teaching is centered on students who do not have an early childhood/kindergarten background which has an impact on the teacher's difficulties in teaching in class. Where the difficulties experienced by the teacher make teaching and learning activities disrupted and cannot run effectively. The formulation of the problem in this study is how difficult it is for teachers to teach students who do not have an early childhood/kindergarten background. This study aims to describe teachers' difficulties in teaching students who do not have an early childhood/kindergarten background. This research uses a qualitative approach, a descriptive research type. The subjects in this study were 1 class I teacher and 17 students who did not have an early childhood/kindergarten background. Data collection techniques through observation and interviews, while data analysis techniques through data reduction, data presentation, and drawing conclusions. The results of this study indicate that the teacher has carried out teaching activities which consist of activities in dealing with individual student differences, determining material that is suitable for the child being faced, choosing the right method, and conducting an evaluation. From these activities, there are difficulties faced by the teacher, namely in the activity of determining material that is suitable for the child being faced in the form of connecting similar subject matter, and using learning aids, then in choosing the right method in the form of associating and embedding the subject matter in everyday life. students' day, and in conducting evaluations in the form of applying new ideas and exploring students' opinions. In addition to these activities the teacher did not experience difficulties in teaching and learning activities. Therefore it can be concluded that teachers experience difficulties in teaching students who do not have an early childhood/kindergarten background.